2005
DOI: 10.2337/diabetes.54.7.1994
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Efficacy of Leptin Replacement in Patients With Generalized Lipodystrophy

Abstract: Ectopic fat accumulation has been implicated as a contributing factor in the abnormal metabolic state of obesity. One human model of ectopic fat deposition is generalized lipodystrophy. Generalized lipodystrophy is a rare disorder characterized by a profound deficiency of adipose tissue with resultant loss of triglyceride storage capacity and reduced adipokines, including leptin. Subjects with generalized lipodystrophy and reduced leptin levels often have an increased appetite leading to hyperphagia. Excess fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
158
2
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(174 citation statements)
references
References 44 publications
11
158
2
3
Order By: Relevance
“…We have presented early evidence to show that this effect of leptin is also true in patients with lipodystrophy [4]. Further studies by our group and others have confirmed this finding [5][6][7][8][9][10].…”
supporting
confidence: 68%
See 1 more Smart Citation
“…We have presented early evidence to show that this effect of leptin is also true in patients with lipodystrophy [4]. Further studies by our group and others have confirmed this finding [5][6][7][8][9][10].…”
supporting
confidence: 68%
“…Although Amgen and then later Amylin provided the recombinant leptin, the data were held and analysed by the academic investigators. r-metHuLeptin therapy was given as a self-administered once-or twice-daily s.c. injection as previously described [4,8,10]. In the earlier years of the protocol, the dose was escalated to the full dose over the first 2 months of treatment.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, leptin levels in the lowest tertile were negatively and independently associated with cardiovascular mortality in both univariate and multivariate analyses [17], including age, serum insulin levels, BMI and monocyte chemoattracting protein, but not other traditional risk factors for CVD. The suggestion of a protective effect of elevated serum leptin levels, in that a preliminary small study (n=17 cases only), together with results from two recent human interventional studies in individuals with relative leptin deficiency and congenital lipoatrophy [26,27], as well as HIV lipoatrophy and the metabolic syndrome [28], showing that leptin-deficient subjects have reduced insulin sensitivity that is improved with leptin administration, prompted us to examine more closely the risk of CVD in women by stratifying for leptin levels below the previously used clinical cut-off levels for hypoleptinaemia [4]. We observed no significantly increased risk of CVD in women with leptin levels <4 ng/ml or <5 ng/ml before and/or after adjustment for confounders.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-eight articles were eligible for full-text review. Of those, 26 were excluded mainly due to not being population-based data (case reports) or review articles and two of these studies were excluded as they represented data sets based on duplicated results from previous studies (20,21). Overall, 12 studies were included for data analysis (14,16,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31).…”
Section: Included Literaturementioning
confidence: 99%